"تأثير القراءات القرآنية بالنحو العربي في سورة الجمعة "دراسة تحليلية تطبيقية: The Effect of Quranic Readings in Arabic Grammar and its Implementation in Surah al-Jumu'ah - Bello, Nuruddeen Ahmad; Bello, Yahya (Jurnal Usuluddin, 2023)
This research focuses on an analytical study, specifically the impact of Quranic readings on Arabic grammar, and its application in surah al-Jumu'ah. The study consists of four sections, starting with the introductory section, which discusses the linguistic and figurative meanings in surah al-Jumu'ah. The first section elucidates the relationship between grammar and Quranic readings, while the second section explores the nouns mentioned in surah al-Jumu'ah from the perspective of grammarians and reciters. The third section examines the verbs mentioned in surah al-Jumu'ah and their interpretation by grammarians and reciters. Finally, the fourth and last section presents the researcher's analysis of the letters mentioned in the surah from the perspective of grammarians and reciters. The study concludes that grammatical factors have a significant influence on Quranic readings. It also highlights specific verbs mentioned in surah Al-Jumu'ah, are yahmilu, hummiluw, infadhuw. The study recommends that grammarians and linguists adjust their rules and derive them from the methodology of the Noble Quran. Additionally, it advises readers to recite the Quran in the narration transmitted by the companions without being concerned about deviating from analogy (qiyas) or adhering to it.